A Phase I Dose‐Escalation Study of the Safety and Pharmacokinetics of Pictilisib in Combination with Erlotinib in Patients with Advanced Solid Tumors. (4th December 2017) - Leong, Stephen; Moss, Rebecca A.; Bowles, Daniel W.; Ware, Joseph A.; Zhou, Jing; Spoerke, Jill M.; Lackner, Mark R.; Shankar, Geetha; Schutzman, Jennifer L.; van der Noll, Ruud; Voest, Emile E.; Schellens, Jan H.M.
Abstract: Background: Epidermal growth factor receptor (EGFR) and phosphatidylinositol 3‐kinase (PI3K) are involved in the proliferation and survival of many cancer types. Enhanced antitumor activity may be achieved through combined inhibition of these pathways. We report results for pictilisib (GDC‐0941, a class I pan‐PI3K inhibitor) plus erlotinib (an EGFR tyrosine kinase inhibitor) in patients with advanced solid tumors. Materials and Methods: A 3 + 3 dose‐escalation study was carried out at a starting daily dose of 60 mg pictilisib on days 1–21 of a 28‐day cycle and 150 mg erlotinib from day 2 of cycle 1. The primary objectives of the study were to assess safety and tolerability, identify dose‐limiting toxicities (DLTs), estimate the maximum tolerated dose, and identify the recommended phase II dose (RP2D). Evaluation of a dose‐expansion cohort at the RP2D was performed. Results: Fifty‐seven patients were treated in the study. All patients experienced at least one adverse event (AE). Grade ≥3 AEs, serious AEs, and deaths were reported in 38 (66.7%), 19 (33.3%), and 4 (7.0%) patients, respectively. DLTs occurred in nine patients across eight cohorts and the RP2D was determined to be 340 mg pictilisib on a "5 days on, 2 days off" schedule plus 100 mg erlotinib. Two patients (3.5%) experienced partial response and 19 (33.3%) had stable disease. Conclusion: Combining pictilisib with erlotinib in patients with advanced solid tumors is feasible; however, antitumor activity is limited. Additional studies may identify patients likely to benefit from combined inhibition of EGFR and PI3K pathways. Abstract : This phase I study was designed to investigate the safety and pharmacokinetics of pictilisib in combination with erlotinib in patients with advanced solid tumors.